The Effect of Service Quality of Online Single Submission to Public Satisfaction and Trust - Wismanu, Rendra Eko; Galih, Aulia Puspaning; Noventi, Ike Arni (Institute of Research and Community Service, University of Brawijaya, 2022)
The state is obliged to serve every citizen and resident to fulfill their basic rights and needs within the framework of public services which are mandated by the 1945 Constitution of the Republic of Indonesia. In the implementation of regional autonomy itself, public service is one of the interesting issues, especially in licensing and non-licensing services organized by local governments are currently competing on providing excellent services based on the implementation of one-stop integrated service (PTSP). As one of the Regional Governments in Indonesia, the Semarang City Government which is one of the City Governments located in Central Java Province has carried out PTSP through the role of DPMPTSP in making efforts to improve the quality of public service delivery based on an Online Single Submission (OSS) for various types of licensing and non-licensing services. The purpose of this study emphasizes quantitative measurement efforts regarding the effect of OSS service quality conducted by the City of Semarang DPMPTSP on the satisfaction and level of public trust. This research uses descriptive research type with quantitative approach with number of respondents in this study are 30 people. The results of this research are that association between the independent variable quality of service to the dependent variable is included in the category of public confidence is very strong. If DPMPTSP service quality has increased by 1 unit, then public satisfaction will increase by 0.961. A sovereign, when the quality of service DPMPTSP increased 1 unit, the satisfaction of the people will increase by 0.373.